THE PROFILE OF EFL TEACHERS’ CANDIDATE TPACK IN NEW NORMAL ERA - Imadul Bilad; Achmad Anang Darmawan; Lina Aris Ficayuma; Ahmad Syafi’I (Journal of English Language Teaching and Islamic Integration, 2024)
TPK, and TPACK constructs, which prompted researchers to question the peculiarities of these three TPACK domains. Referring to TPACK's weaknesses in terms of precision and heuristic values, they concluded that TPACK may be theoretically effective but provides limited practical benefits for teachers, researchers, and administrators. The high level of Technological Content Knowledge (TCK) among prospective student teachers in their TPACK profile has significant implications. This indicates that these students possessed a strong understanding of how to effectively integrate ttechnology into their teaching practices, specifically in relation to the content they were teaching.